THE URGENCY OF USING FLIPCHART MEDIA AS A SIMPLE AND EFFECTIVE ALTERNATIVE LEARNING MEDIA - JUNIARSI SALPIA (Teaching and General Education Studies, 2026)
Learning media is an important part of the educational process because it functions as a tool to convey messages from teachers to students so that the material delivered can be received effectively. In the era of digital technology advancement, the use of electronic-based media such as PowerPoint, learning videos and other online learning media is increasingly growing. However, the limited facilities available at some schools require the use of alternative media that are simple, economical, and still effective. This research aims to review the urgency of using flipchart media as an alternative visual learning media that is efficient and remains relevant to be applied in learning, especially in elementary schools. This study uses a literature study approach by analyzing the concept of learning media, flipchart characteristics, usage strategies, integration with active learning methods, and the results of previous research. The study results show that flipcharts have advantages in increasing student motivation, attention, activeness, and learning outcomes. Furthermore, flipcharts have proven effective because they can present material systematically, realistically, and interactively without the need for technological devices. Various previous studies have proven that the use of flipcharts can substantially increase learning completion and student participation. Based on this, flipchart media is suitable for use as an alternative learning media that is simple but effective in supporting the creation of active, interactive, and meaningful learning